2021
DOI: 10.7324/japs.2021.110804
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective potency of anthocyanin-rich extract of red cabbage against isoproterenol-induced myocardial infarction in experimental animals

Abstract: The current research was realized for the cardioprotective effect of anthocyanin-rich extract of red cabbage (ARERC) on isoproterenol-induced (ISO) myocardial infarction (MI) in rats. Total phenolic, anthocyanin content, and antioxidant activity were assessed in ARERC. ARERC acute toxicity was evaluated. The results revealed that ARERC contains a high amount of total phenolic (633.9 mg gallic acid equivalents/100 g) and total anthocyanin (618.2 mg Cy3G/100 g) in association with antioxidant activity against (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…The extensive inflammation seen in the heart tissues shows the cardiotoxic effect of the extract. Several tropical plant species have been reported to possess cardiotoxic effects when used as herbal remedies [17,18]. It was reported that an aqueous extract of J. traquebareinsis leaf showed cardioprotective effects against isoproterenol-induced myocardial infarction in rats.…”
Section: Discussionmentioning
confidence: 99%
“…The extensive inflammation seen in the heart tissues shows the cardiotoxic effect of the extract. Several tropical plant species have been reported to possess cardiotoxic effects when used as herbal remedies [17,18]. It was reported that an aqueous extract of J. traquebareinsis leaf showed cardioprotective effects against isoproterenol-induced myocardial infarction in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, Justicia carnea is used in the management of inflammation, gastrointestinal disorders, respiratory tract infection, fever, pain, diabetes, diarrhea, liver diseases, rheumatism and arthritis (Badami et al, 2003;Corrêa & Alcântara, 2012). They also possess antiinflammatory, anti-allergic, anti-tumoral, anti-viral and analgesic activities (Radhika et al, 2013).…”
Section: Importance and Uses Of Justicia Carneamentioning
confidence: 99%